Magnetic Retention for Obturators - Samira K. Al-Salehi, BDS, MFDS, DGDP; Ian D. Calder, HNC; (Journal of Prosthodontics, 2007)
Prosthetic rehabilitation can be challenging in cases of maxillectomy or developmental defect.